Implementasi Algoritma Lucifer untuk Autentikasi Sound Chat - Ade Sani Afrianda (ADA Journal of Information System Research, 2024)
Voice chat is one of the ways used to send a message through a chat application, where voice chat contains messages in the form of voice. There are problems in the process of sending voice chats, where in the delivery process there can be damage or manipulation of sound that can be done by parties who are not involved in the voice chat. In this case, security is needed to maintain the authenticity of the chat voice to avoid damage or what can be done by non-existent parties. Cryptographic techniques can be used to maintain the authenticity of voice chats with encryption and decryption processes so that they can minimize damage or damage to voice chats that can be done by parties who do not. The lucifer algorithm is an algorithm that can perform cryptographic techniques, where the lucifer algorithm encrypts data that has been divided into blocks. This study uses the lucifer algorithm for the encryption and decryption process. A voice chat will be encrypted using the lucifer algorithm to produce ciphersound. This process can increase the security and authenticity of the chat voice in the sending process and will not arouse suspicion from other parties who are not responsible for knowing the authenticity of the chat voice.